Entrepreneurship and the cities in a knowledge-based perspective: evidences from EU. Issue 3 (16th July 2019) - Penco, Lara; Ivaldi, Enrico; Bruzzi, Carolina; Musso, Enrico
Abstract : Purpose: The purpose of this paper is to answer the following research questions: Is the knowledge of a city environment a stimulus for entrepreneurship? Which knowledge profiles of cities are more propulsive in order to stimulate entrepreneurship? Design/methodology/approach: In order to answer the aforementioned research questions, two multidimensional indexes have been created: Knowledge-Based City Developing Entrepreneurship and Entrepreneurship (ENT). The sample includes all capital cities in the EU28. The presence of cities from EU28 countries is important to foster the entrepreneurial attitude in each European Country. The authors have also included 32 non-capital cities in the EU that are important hubs, contributing to a sample formed of 60 cities. Findings: The empirical results show that the social and cultural environment may significantly improve the entrepreneurship in EU cities, more than others factors that are usually connected to economic development. Originality/value: The work tries to contribute to the debate on urban economic development and entrepreneurship, providing implication for academics and urban policy makers.